Building Financial Capability of MSMEs through Financial Factor Analysis and its Effect on Lending Policy on P2P Lending Platforms - Wulandari, Putu; Novianti, Nurlita; Puspita, Ayu Fury (The International Journal of Accounting and Business Society, 2023)
Purpose — This study aimed to analyze the effect of MSME financial factors, which consist of credit score, business turnover, leverage ratio, number of loans, company size, and profitability, on P2P lending policies. Design/methodology/approach—This study uses a quantitative research approach to test research hypotheses relevant to the research phenomenon. The logistic regression data analysis technique examined the factors that influence credit-granting decisions. Practical implications—This research's practical implications are that it will benefit MSME business actors by preparing important financial data to obtain alternative funding sources other than conventional financial services. Originality/value—This study reveals the financial variables that are important to consider in providing P2P loans to MSMEs, which is expected to provide hope for MSMEs to develop financial capabilities and increase business growth.   Paper type — Case study